Watt-scale super-octave mid-infrared intrapulse difference frequency generation. Issue 1 (December 2018) - Gaida, Christian; Gebhardt, Martin; Heuermann, Tobias; Stutzki, Fabian; Jauregui, Cesar; Antonio-Lopez, Jose; Schülzgen, Axel; Amezcua-Correa, Rodrigo; Tünnermann, Andreas; Pupeza, Ioachim; Limpert, Jens
Abstract The development of high-power, broadband sources of coherent mid-infrared radiation is currently the subject of intense research that is driven by a substantial number of existing and continuously emerging applications in medical diagnostics, spectroscopy, microscopy, and fundamental science. One of the major, long-standing challenges in improving the performance of these applications has been the construction of compact, broadband mid-infrared radiation sources, which unify the properties of high brightness and spatial and temporal coherence. Due to the lack of such radiation sources, several emerging applications can be addressed only with infrared (IR)-beamlines in large-scale synchrotron facilities, which are limited regarding user access and only partially fulfill these properties. Here, we present a table-top, broadband, coherent mid-infrared light source that provides brightness at an unprecedented level that supersedes that of synchrotrons in the wavelength range between 3.7 and 18 µm by several orders of magnitude. This result is enabled by a high-power, few-cycle Tm-doped fiber laser system, which is employed as a pump at 1.9 µm wavelength for intrapulse difference frequency generation (IPDFG). IPDFG intrinsically ensures the formation of carrier-envelope-phase stable pulses, which provide ideal prerequisites for state-of-the-art spectroscopy and microscopy. Mid-infrared photonics: bright broadband source A table-top-sized, coherent light source that offers a compact and bright alternative to a synchrotron in the 4−18 µm spectral range has been developed by a German-US research team. The team used a novel ultrashort (16 fs) pulse, high power Tm-doped fiber laser operating at 1.9 µm to induce a nonlinear frequency downconversion process called intrapulse difference frequency generation in a crystal of GaSe. The broad spectral coverage and high brightness render this mid-infrared source a unique tool for state-of-the art spectroscopy and microscopy. The team says that the compactness and simplicity of the presented approach brings exciting prospects for the future accessibility, in particular for emerging applications that are currently addressed only with mid-infrared beamlines in large-scale synchrotron facilities.